Nuevos registros del temazate rojo (mammalia: Artiodactyla: cervidae: Mazama temama) en el estado de Puebla, México - Ramírez Bravo, O. Eric; Hernández-Satin, Lorna (Instituto de Ecología, A.C., 2012)
In Puebla, the distribution of Central American red brocket deer (Mazama temama) is unknown due lack of studies. With interviews and field work, we got 30 new records for the Sierra Madre Oriental and Sierra Negra. Our results give information about its distribution, including areas where it was considered extinct. This confirms the necessity to generate a strategy for its conservation in the state.